Alfred Fletcher's campaign for black smoke abatement, 1864–96: Anticipating the 1956 Clean Air Act. (2nd January 2021) - Reed, Peter
Abstract : Many smog episodes occurred during the nineteenth century because of the steadily rising consumption of coal for industrial furnaces, commercial ovens and domestic hearths, but the few legislative efforts to abate black smoke proved ineffectual. It was only in 1956, and following the major London smog episode of 1952, that the government was finally forced into action and parliament approved the Clean Air Act. But two important elements of the 1956 legislation were key parts of an earlier campaign conducted by Alfred Fletcher between 1864 and 1896 and while he was working for the Alkali Inspectorate. The Inspectorate had expected black smoke to be added to the list of regulated noxious vapours but governments and parliament resisted. Access to Fletcher's private diaries reveal how he remained a leading advocate for abatement of black smoke, and used his position as Chief Inspector from 1884 to conduct a multi-pronged campaign both inside and outside the Inspectorate that included promoting gas as a fuel and the technical evaluation of cleaner appliances.